Self-Initiated Actions Under Different Choice Architectures Affect Framing and Target Evaluation Even Without Verbal Manipulation - Onuki, Yutaro; Honda, Hidehito; Ueda, Kazuhiro (Frontiers in Psychology, 2020)
Logically equivalent but different descriptions (i.e., manipulation of verbal expressions) affect decision making in a phenomenon known as the framing effect. A choice architecture changes decision-makers’ actions, which in turn create different frames, but little is known about whether the frame created by their action can change their judgments. We examined whether self-initiated action induced by a choice architecture changed evaluations. In two experimental studies (N = 271), we found that self-initiated actions whose final goal was completely the same and for which no verbal expressions were manipulated led to different evaluations. In particular, we found that a difference in the placement of rewards, which required participants to behave differently, changed their ratings of satisfaction with the rewards. This study provides evidence that the framing effect can occur without verbal manipulation. This finding advances our understanding of how participants’ actions lead to different evaluations.